Space Flight-Promoted Insulin Resistance as a Possible Disruptor of Wound Healing - Strollo, F.; Gentile, S.; Pipicelli, A. M. V.; Mambro, A.; Monici, M.; Magni, P. (Frontiers in Bioengineering and Biotechnology, 2022)
Microgravity is known to cause low-grade inflammation through muscle unloading. These two factors typically lead to insulin resistance through increased fat to fat-free mass ratio. Far from having a mere storage function, the adipose tissue can be referred to as a diffuse endocrine organ secreting several intertwined signals which contribute to appetite and energy regulation, immune-metabolic balance, and wellbeing. When expanding well above its normal volume or outside its natural boundaries, adipose tissue becomes dysfunctional, leading to excessive oxygen demands. Then, it attracts macrophages bound to get rid of damaged cells and releasing high amounts of pro-inflammatory cytokines, which further increase oxidative stress both locally and systemically. Obesity and diabetes mellitus are well-known insulin-resistant and chronic inflammatory states, associated with increased fat to fat-free mass ratio, increased cardiovascular risk and impaired cutaneous wound healing. The latter complication results from the lack of optimal insulin activity, normally needed for tissue repair via adequate microvascular recruitment and protein anabolism. Moreover, microgravity is also associated with a negative impact on gut microbiota, both in experimental animals and humans. This further increases the risk for progressively worsening insulin resistance, thus causing more significant wound healing problems. Further studies are still required to clarify the connection between insulin resistance and wound healing during space flight, addressing the ability of physical, endocrine/metabolic, and pharmacological countermeasures, and nutritional strategies to prevent long-term detrimental effects on tissue repair and life-threatening cardiovascular events commonly linked to insulin resistance